Effectiveness of hypertensive gymnastics physical exercise on lowering blood pressure in hypertensive patients - Maria Kurni Menga; Yuriatson Yuriatson; Idawati Binti Ambo Hamsa (Journal Interdisciplinary Health, 2025)
Introduction: Hypertension is a primary global health concern often referred to as a "silent killer" due to its asymptomatic progression and high risk of cardiovascular complications. Non-pharmacological interventions, such as structured physical exercises, have gained attention as effective alternatives to control blood pressure levels. This study aimed to determine the effectiveness of hypertension exercise in lowering blood pressure among elderly hypertensive patients. Methods: A descriptive case study design involved two hypertensive patients aged 60–65 at Tamalanrea Health Center, Makassar. The intervention consisted of a three-day hypertension exercise regimen conducted twice daily. Blood pressure was measured using a digital sphygmomanometer before and after each exercise session. Additional data for the exercise program was collected using questionnaires, observation sheets, interviews, and standard operating procedures (SOPs). Results: The findings revealed a significant reduction in systolic and diastolic blood pressure. Respondent 1 experienced a decrease from 170/72 mmHg to 130/70 mmHg, while Respondent 2's blood pressure reduced from 194/100 mmHg to 140/75 mmHg after the intervention. Conclusion: Hypertension-specific physical exercise effectively reduced blood pressure among hypertensive patients. It is recommended as a safe, low-cost, and accessible non-pharmacological therapy, especially for older people